Acineta nitocrae sp. n. (Ciliophora, Suctoria) —комменсал Nitocra hibernica - Довгаль, И.В. (Вестник зоологии, 1984)
Acineta nitocrae sp. n. is described from harpacticoid furca of Nitocra hibernica. From similar species it differs by elongated, slightly flattened lorica, stronger actonophores, short, curved weakly lineated stalk and elongated macronucleus. Type locality: left bank of Dnieper near Kiev.